A novel approach to improve the efficiency of national rural employment scheme employees using WBASN - Rajasekar, P.; Pushpalatha, M. (International Journal of Engineering and Technology, 2018)
Health monitoring of human being can be done using implant or wearable sensors. Making use of these sensors to form a network are aptly called as Wireless Body Area Sensor Networks (WBASN). Better performance and energy saving can be accomplished in a challenging way in this type of network. National Rural Employment Guarantee Act in India provides employment for people in rural areas. This involves more intense physical work in the open environment. People involved in this work tend to feel fatigue if they work for prolonged duration. We have conducted experiments in several scenarios to determine the stamina level of employed people and proposed ways to provide how man power can be efficiently improved by giving optimal break time and energy supplement drinks to improve the stamina level. Moreover energy of sensors may be efficiently improved by compressing the data before transmitting them to servers by suitable algorithm as discussed in our paper.